Fetal AED Exposure and Cognitive Outcome at Age 6 - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Investigators at Emory University, Atlanta, GA and multiple centers in the USA and UK conducted a prospective study of the effects of antiepileptic drug (AED) monotherapy (carbamazepine, lamotrigine, phenytoin, or valproate) on the intelligence quotient (IQ) at 6 years of age (age-6 IQ).